The constitutional logic of affirmative action - Fiscus, Ronald Jerry (Duke University Press, 1992)
The Central Argument: The Meaning of Racial Correlations Given Nonracist Assumptions and Original Positions. Of Molecules and Mobility. Required Assumptions and the Court. Race and Cultural Ethnicity Distinguished -- The Innocent Persons Argument Examined: The Innocent Person Shown to Be Guilty When Claiming Proportional Set-Aside Positions. The Innocent Persons Argument and the Court. The Misplaced Emphasis on Innocence and Blame -- Proportionate and Disproportionate Quotas, The Key Distinction: Formalism. Entitlement. The Supreme Court and the Proportionality Principle. Related Constitutional Arguments -- Scholarly Comment and the Proportionality Principle: Ronald Dworkin and the Rights of Whites -- Applying the Principles: The Supreme Court and Affirmative Action: In General. Local versus National Standards. Applicant versus Labor Pool. The Complications of Seniority and Repeat Applications in Hiring and Promotions. Seniority, Repeat Applications, and Layoffs: The Stotts Case Revisited